(untitled) (Journal of Tropical Resources and Sustainable Science (JTRSS), 2021)
Alum natural mineral salt is the world’s leading crystal deodorant which works in removing unpleasant body smell. Some other products attempt to block the sweat pores with harmful chemicals such as aluminum chlorohydrates or aluminum zirconium. However, crystal is hypoallergenic deodorant that is healthy, safe, and effective in inhibiting odor formation on the axillary. The light scent infused with natural essential oils might enhance the properties of the crystal deodorant and its antimicrobial activity in fighting against body odor bacteria. This study was conducted to evaluate the potential antimicrobial activity of both citrus essential oils and alum salt. The essential oils were extracted from Citrus aurantifolia, and Citrus sinensis peels by water-steam distillation and analysed using gas chromatography-mass spectrometry (GC-MS). Antibacterial assay against Escherichia coli was carried out on the extracted essential oils using paper disc diffusion assay. Results showed that no lead and cadmium constituents were detected, while low concentration of iron (0.993 ± 0.0059 ppm) and copper (0.134 ± 0.0078 ppm) were detected in the crystal salt (15% w/v). D-limonene, decanal and citral were major components responsible for the citrus scents aroma. The C. aurantifolia essential oil and 15% w/v alum salt were active against E. coli with inhibitory zones at 7.23 ± 0.15 mm and 11.13 ± 0.51 mm respectively. The citrus scented crystal deodorant was successfully developed and tested.